Analisis Hubungan Faktor Fisik dan Individu terhadap Prevalensi Keluhan Musculoskeletal Disorder (MSDs) pada Pekerja CV Bengkel Otomotif Tahun 2022 - Fajri, Hamzah Fansuri; Modjo, Robiana (UI Scholars Hub, 2023)
Complaints of musculoskeletal disorders (MSDs) in general can occur due to contraction or excessive loading of muscles or bones. One example of an activity that can trigger the incidence of musculoskeletal disorders (MSDs) is manual material handling work. Manual material handling work is still commonly found in the work done at CV Bengkel Otomotif. This study focuses on looking at the relationship between physical and individual variables with complaints of musculoskeletal disorders (MSDs) in CV Bengkel Otomotif workers. This research is a cross-sectional study with quick exposure check and nordic body map instruments. Of the 60 workers who became respondents to the study, it was found that 38 workers (63.3%) had complaints. The part of the body that experienced the most complaints was the waist (25 workers). The results showed that there was a relationship between the variable body mass index (p value = 0.004), and exercise habits (p value = 0.004) with complaints of musculoskeletal disorders (MSDs).